Using gamma irradiation to attenuate the effects caused by drying or freezing in Macrolepiota procera organic acids and phenolic compounds - Fernandes, Ângela (2014)
Macrolepiota procera (Scop.) Singer, commonly parasol mushroom, is an appreciated wild edible species. Due to its very perishable nature, M. procera must be processed to extend its shelf life. The chemical changes caused by common processing types should be avoided to maintain the wholesomeness of organoleptic features. Irradiation might be used as a preservation methodology due to its safety, cost effectiveness and ability to ensure hygienic and sensory quality. Furthermore, when combined with other preservation technologies, irradiation exhibits an attenuating effect over the chemical changes caused by some of those treatments per se. Herein, the effects of irradiation of M. procera processed samples (frozen, dried and fresh) were evaluated considering changes in organic acid and phenolic compound profiles. Detected contents of phenolic were much lower than those of organic acids. Differences caused by processing type, specifically the lower levels of total organic acids and phenolic acids in dried and frozen samples, were larger than those observed for stronger irradiation doses, which did not cause remarkable changes, except for a slightly lower content of phenolic acids in non-irradiated samples. This larger effect was statistically confirmed in the performed linear discriminant analysis. Besides its slighter influence, irradiation showed potential usefulness to be used as complementary preservation technology since it attenuated the lowering effects of dehydration and freeze treatment over specific organic acid contents.